2022
DOI: 10.1089/whr.2021.0111
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Patterns and Anxiety Factors Among Women Expressing Perinatal Depression

Abstract: Background: Relationships among perinatal depression occurring a number of weeks before and after childbirth and smoking have been identified. Depression may lead to the inability to abstain from smoking during pregnancy. Objectives: This study aims to determine factors affecting smoking during pregnancy revealing potential relationships between depression and smoking patterns during and after pregnancy. Methods: A total of 206 mothers partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…In the present study, pregnant women's perinatal depression was associated with a lower educational level and a worse economic status, whereas women's age, nationality, and marital and employment status were not considerably related to depression during pregnancy. In agreement with our results, several previous studies have also shown that pregnant women's perinatal depression is related to a lower educational level and a worse economic status [73][74][75][76]. However, some studies have demonstrated conflicting results, reporting a higher or a lower prevalence of perinatal depression of pregnant women [77].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, pregnant women's perinatal depression was associated with a lower educational level and a worse economic status, whereas women's age, nationality, and marital and employment status were not considerably related to depression during pregnancy. In agreement with our results, several previous studies have also shown that pregnant women's perinatal depression is related to a lower educational level and a worse economic status [73][74][75][76]. However, some studies have demonstrated conflicting results, reporting a higher or a lower prevalence of perinatal depression of pregnant women [77].…”
Section: Discussionsupporting
confidence: 92%
“…). As priorly reported (77,78,81), tobacco use (mean RR=1.09, sd=0.01, Figure 3c), unplanned pregnancy (RR=1.03, sd=0.01, Figure 3d), and being single (RR=1.02, sd=0.01, Figure 3e)…”
Section: Figure 3bsupporting
confidence: 67%
“…In this context, a targeted approach should be taken to build awareness of the harmfulness of hookah smoking during pregnancy. Pregnancy has been regarded as a “teachable moment” 43 and smoking cessation is hard, even during pregnancy 33 . A hookah can be seen as a potential alternative and vehicle for smoking cessation during pregnancy, but special caution needs to be adopted in preventing such switching between other tobacco products and hookah smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Having an infant with a low birth weight was positively associated with PPD symptoms and similar findings were reported in a previous study. 33 Although a healthy newborn sparks a joyous occasion, a newborn in need of medical attention can lead the mother to PPD symptoms. 34 Room-sharing with an infant also increased the odds of having PPD symptoms in mothers.…”
Section: Discussionmentioning
confidence: 99%